The Composite Index Berbasis Variabel Makro: Analisis Kausalitas Data Time Series - Irdha Yusra (Universitas Negeri Padang, 2019)
The composite index is one indicator used by the government in making policies in the economic field. Previous research has proven the influence of macro variables on the composite index. The macro variables used in this study are inflation, SBI interest rates, and the exchange rate Indonesian Rupiah (IDR) to United States Dollar (USD). Furthermore, the aim of this paper is to predict the composite index based on macro variables in Indonesia. Time series data is taken from monthly data for three years (2015-2017). The design of this study is causal research estimated using time series regression. The results showed that inflation did not significantly influence the composite index. The result suggests that inflation is still quite stable during that period. Meanwhile, interest rates on Bank Indonesia certificates and exchange rates have a significant effect on the composite index. Thus, the ability of macro variables in predicting composite index can only be determined by SBI interest rates and exchange rates.